Service Quality Leadership of Emergency Department of RSUD K.R.M.T Wongsonegoro (K.R.M.T Wongsonegoro District Hospital) - Ariyani, Ima; Jati, Sutopo Patria; Arso, Septo Pawelas (Universitas Negeri Semarang, 2021)
Leadership style in hospital environment affects towards service quality. Therefore, chief of RSUD K.R.M.T Wongsonegoro conducts several efforts to increase its service quality especially at Emergency Department. The purpose of this research is to know the most-used leadership style by the chief of RSUD K.R.M.T Wongsonegoro that affects towards service quality at the Emergency Department. This research uses qualitative research method and selects the informant by using purposive sampling technique. The main informants consist of 4 (four) persons, and triangulation informants consist of 4 (four) persons. The data collection techniques used by this research are in-depth interview and document study. Based on the research results, there were two leadership styles found during the research. Firstly, it showed that the most dominant leadership style used by the chief and affected on the employeesÃ¢â‚¬â„¢ discipline in order to increase the service quality at the Emergency Department was transformational leadership style, where the chief encouraged, inspired, and appreciated the employees, so they were able to carry out the applicable policies, because they felt they were appreciated. Secondly, transactional leadership style, by implementing award and punishment systems, the employees were obey the rules they expected to get the award if they executed their job well.Ã‚Â Key Words: leadership, quality enhancement, hospitalDocument: 44 (2010-2019)